A new species of Clypeodytes Régimbart, 1894 from China (Coleoptera, Dytiscidae: Bidessini) - Mai, Zuqi; Jiang, Zhuoyin; Hu, Jian; Hendrich, Lars; Jia, Fenglong (Zootaxa, 2022)
The diving beetle Clypeodytes limpidus sp. nov. is described from western Yunnan, China. It is the second known species of the genus Clypeodytes Régimbart, 1894 from China and belongs to the subgenus Hypoclypeus Guignot, 1950. It can be distinguished from C. bufo (Sharp, 1890), the only other Chinese Clypeodytes species, by the shape of the median lobe, the more rounded body and the elytral pattern. A Chinese specimen of C. bufo is illustrated, and the species is recorded for the first time for Laos.